![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{A}{x-2}=\dfrac{x^2+3x+2}{x^2-4}\)
\(\Leftrightarrow\dfrac{A}{x-2}=\dfrac{\left(x+2\right)\left(x+1\right)}{\left(x-2\right)\left(x+2\right)}\)
\(\Leftrightarrow\dfrac{A}{x-2}=\dfrac{x+1}{x-2}\Leftrightarrow A=x+1\)
b) \(\dfrac{M}{x-1}=\dfrac{x^2+3x+2}{x+1}\)
\(\Leftrightarrow\dfrac{M}{x-1}=\dfrac{\left(x+1\right)\left(x+2\right)}{x+1}\)
\(\Leftrightarrow\dfrac{M}{x-1}=x+2\Leftrightarrow M=\left(x-1\right)\left(x+2\right)=x^2+x-2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x(x + 4) - 3x - 12 = 0
x(x + 4) - 3(x + 4) = 0
(x + 4)(x - 3) = 0
x = -4 hoặc x = 3
b) 2x(x - 4) - x + 4 = 0
2x(x - 4) - (x - 4) = 0
(x - 4)(2x - 1) = 0
x = 4 hoặc x = 1/2
c) 5x(x - 3) - x + 3 = 0
5x(x - 3) - (x - 3) = 0
(x - 3)(5x - 1) = 0
x = 3 hoặc x = 1/5.
a) x(x + 4) - 3x - 12 = 0
x(x + 4) - 3(x + 4) = 0
(x + 4)(x - 3) = 0
x = -4 hoặc x = 3
b) 2x(x - 4) - x + 4 = 0
2x(x - 4) - (x - 4) = 0
(x - 4)(2x - 1) = 0
x = 4 hoặc x = 1/2
c) 5x(x - 3) - x + 3 = 0
5x(x - 3) - (x - 3) = 0
(x - 3)(5x - 1) = 0
x = 3 hoặc x = 1/5.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^2-2x+3\right)\left(\frac{1}{2x}-5\right)\)
\(=\frac{x^2}{2x}-5x^2-\frac{2x}{2x}+10x+\frac{3}{2x}-15\)
\(=\frac{x^2}{2x}-5x^2-16+10x+\frac{3}{2x}\)
\(=-5x^2+\frac{x^2}{2x}+\frac{20x^2}{2x}+\frac{3}{2x}-16\)
\(=-5x^2+\frac{x^2+20x+3}{2x}-16\)
học tốt
(x^2-2x+3)(1/2x-5)=1/2x^3-5x^2-x^2+10x+3/2x-15=1/2x^3-6x^2+11,5x-15
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
Để $x^4+2x^3-ax^2+5x+b$ chia $x^2+x-2$ dư $3x+4$ thì:
$x^4+2x^3-ax^2+5x+b=(x^2+x-2)Q(x)+3x+4$ với $Q(x)$ là đa thức thương.
$\Leftrightarrow x^4+2x^3-ax^2+5x+b=(x-1)(x+2)Q(x)+3x+4$
Cho $x=1$ thì:
$8-a+b=7\Leftrightarrow a-b=1(1)$
Cho $x=-2$ thì:
$-10-4a+b=-2\Leftrightarrow -4a+b=8(2)$
Từ $(1); (2)\Rightarrow a=-3; b=-4$
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\\ a,=6x^4y^4-x^3y^3+\dfrac{1}{2}x^4y^2\\ b,=4x^3+5x^2-8x^2-10x+12x+15\\ =4x^3-3x^2+2x+15\\ 2,\\ a,=7\left(x^2-6x+9\right)=7\left(x-3\right)^2\\ b,=\left(x-y\right)^2-36=\left(x-y-6\right)\left(x-y+6\right)\\ 3,\\ \Leftrightarrow x\left(x^2-0,36\right)=0\\ \Leftrightarrow x\left(x-0,6\right)\left(x+0,6\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=0,6\\x=-0,6\end{matrix}\right.\)
?/
đâu bài nào